Submarine Moraines in Southeast Greenland Fjords Reveal Contrasting Outlet‐Glacier Behavior since the Last Glacial Maximum. Issue 6 (19th March 2019) - Batchelor, C. L.; Dowdeswell, J. A.; Rignot, E.; Millan, R.
Abstract: Knowledge of the past behavior of the outlet glaciers of Southeast (SE) Greenland is necessary to understand and model spatial differences in the response of the Greenland Ice Sheet (GIS) to climatic changes. Here we use bathymetric data to map the distribution of more than 50 major moraines in SE Greenland fjords. Inner‐fjord moraines are widespread along the SE Greenland margin, occurring in 65% of the surveyed fjords. We identify, for the first time, nine midfjord moraines that span the approximately 150‐km‐long eastern margin of the Julianehåb Ice Cap. In contrast, midfjord moraines are generally absent from the deeper and wider fjords of the SE GIS. The variable distribution of midfjord moraines along the SE Greenland margin reveals contrasting behavior of the SE GIS and the eastern Julianehåb Ice Cap during the last deglaciation, which probably reflects differences in fjord geometry and exposure to ocean heat. Key Points: We use bathymetric data to identify major moraine ridges in Southeast Greenland fjords Inner‐fjord moraines, which were probably formed during the Neoglacial, are widespread along the Southeast Greenland margin Midfjord moraines are present beyond the Julianehåb Ice Cap yet are generally absent from the Southeast Greenland Ice Sheet margin